Discrimination grounds and personalised pricing: Consumer perceptions of fairness, norm alignment, legality, and trust in markets - Kimia Heidary; Jean-Pierre van der Rest; B. H. M. Custers (Internet Policy Review, 2024)
This article explores consumer perceptions of different grounds by which online prices can be personalised. We conducted a survey among Dutch consumers (n = 727) presenting them with 25 segmentation bases, drawing from legally permissible and legally prohibited grounds. We then ranked these bases and accompanying consumer perceptions across five dimensions: fairness, alignment with personal norms, alignment with social norms, perceived legality, and trust in markets. We find that while consumer perceptions generally align with what is currently prohibited in law, there are some "new" grounds, in particular intelligence and physical appearance, that elicit similar negative perceptions as legally prohibited grounds. This raises questions regarding the further regulation of personalised pricing. We discuss pros and cons of updating legislation to better reflect (new) ethical and social norms.
Keywords: 300; Personalised pricing; Consumer profiling; Price discrimination; Norms; Anti-discrimination law